OPTIMALISASI KINERJA UNIT PELAKSANA TINGKAT DAERAH BALAI LATIHAN KERJA DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN MAJENE - Alim, Muhammad; Ismail, Imran; Nurkaidah, Nurkaidah (Jurnal Paradigma Administrasi Negara, 2020)
The purpose of the study was to determine the improvement in employee performance on public services, employee performance appraisal and the benefits of employee performance appraisal at the UPTD BLK Majene Regency. In this study a qualitative approach was used with analytical descriptive method. Data were obtained from a number of informants consisting of: the head of the Majene UPTD BLK, the Secretary of the UPTD BLK of Majene Regency, the Employees and Community of Majene District who attended the training. The results of this study are: The performance of employee services in the Human Resources Empowerment and Empowerment Agency of Majene Regency is fairly good. This is based on the results of research with three indicators, responsiveness, responsibility and accountability. And the assessment of employee performance in the UPTD BLK of Majene Regency is fairly good. This is based on the results of research with three indicators, namely: Relevance of performance appraisal, Sensitivity of performance assessment